2016
DOI: 10.1021/acscatal.5b02755
|View full text |Cite
|
Sign up to set email alerts
|

C–H Difluoroalkylation of Aldehyde Hydrazones with Functionalized Difluoromethyl Bromides under Copper Catalysis

Abstract: The Cu-catalyzed direct difluoroalkylation of aldehyde hydrazones with functionalized difluoromethyl bromides is described. The reaction yields stereodefined α,α–difluoro-β-keto hydrazones under mild conditions and can be carried out at a scale that opens up the possibility of practical applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(24 citation statements)
references
References 49 publications
(21 reference statements)
2
22
0
Order By: Relevance
“…[12] To gain some insight into the mechanism of this reaction, we carried out as eries of control experiments.F irst, the subjection of 1.0 equivalents of 2,2,6,6-tetramethyl-1-piperidinyloxy (TEMPO) to the standard reaction conditions completely inhibited the reaction (Scheme 3a), and the coupling product 10 between TEMPO and difluoroalkyl radical was detected in 14 and 18 %yield, respectively,with or without the addition of 1a. [13] Both results indicated that ar adical pathway was possibly involved. To further confirm this speculation, the radical clock 11 was subjected to the standard reaction conditions,giving the ring-opening product 12 in 25 %yield (Scheme 3b), thus further demonstrating that af ree difluoroalkyl radical was generated in the catalytic cycle.…”
Section: Angewandte Chemiementioning
confidence: 94%
See 1 more Smart Citation
“…[12] To gain some insight into the mechanism of this reaction, we carried out as eries of control experiments.F irst, the subjection of 1.0 equivalents of 2,2,6,6-tetramethyl-1-piperidinyloxy (TEMPO) to the standard reaction conditions completely inhibited the reaction (Scheme 3a), and the coupling product 10 between TEMPO and difluoroalkyl radical was detected in 14 and 18 %yield, respectively,with or without the addition of 1a. [13] Both results indicated that ar adical pathway was possibly involved. To further confirm this speculation, the radical clock 11 was subjected to the standard reaction conditions,giving the ring-opening product 12 in 25 %yield (Scheme 3b), thus further demonstrating that af ree difluoroalkyl radical was generated in the catalytic cycle.…”
Section: Angewandte Chemiementioning
confidence: 94%
“…To further improve the yield and considering the ligands coordinating onto the catalyst could tune its activity,s everal ligands (L1-L8)h ad been examined in this reaction system, but L1 still proved to be the optimal (entries 5-11). Further catalyst screening indicated that NiCl 2 ·6 H 2 O, NiCl 2 (dppe), NiCl 2 ·DME, and NiBr 2 (PPh 3 ) 2 could afford comparative yields,a nd Ni(NO 3 ) 2 ·6 H 2 O [8c] turned out to be the best choice (entries [12][13][14][15][16][17][18][19]. Notably, aslight increase of 2a to 2.0 equivalents (1a/2a/3a= 1.5:2:1) further improved the yield of 4a to 93 %( entry 20).…”
mentioning
confidence: 99%
“…[115] Finally,o xidation of aminyl radical F by gold species D followed by deprotonation affords the desired difluoromethylated product G. Thea uthors [113] also showedb yD FT calculations that products with the C=Nb ond in E configurationa re lower in energy than those with Z configuration, and that isomerization activation energy usually amountst om ore than 20 kcal mol À1 .T he Au photocatalyst favors formation of the thermodynamic E-configured product. Boyssi, Monteiro and collaborators [116] have recently reported on the CÀHd ifluoroalkylation of aldehyde hydrazones with BrCF 2 CO 2 Et under Cu catalysis. The protocol employs CuCl, 1,10-phenanthroline as ligand, K 2 CO 3 as base in MeCN as solvent at 80 8C.…”
Section: Difluoromethylation Of Hydrazones and Diazoniums Altsmentioning
confidence: 99%
“…Several research groups reported the synthesis of mono fluorinated and difluorinated pyrazoles (Figure ) . In 2014, Sandford and co‐workers pioneered the synthesis of difluorinated pyrazoles under microwave irradiation condition, and obtained a mixture of mono‐ and di‐fluorinated compounds in low yield (Figure a).…”
Section: Introductionmentioning
confidence: 99%
“…Several research groups reported the synthesis of mono fluorinated [7][8][9][10] and difluorinated pyrazoles ( Figure 2). [11][12][13][14][15][16][17][18] In 2014, Sandford and co-workers [16] pioneered the synthesis of difluorinated pyrazoles under microwave irradiation condition, and obtained a mixture of mono-and di-fluorinated compounds in low yield (Figure 2a). Walton [17] reported the single example of difluorinated pyrazole compound under thermal difluoro pyrazol-3-imines derivatives in high yield.…”
Section: Introductionmentioning
confidence: 99%